Dampak Aplikasi Mobile Health (Mhealth) Terhadap Perilaku dan Outcome Kesehatan Ibu Hamil: Tinjauan Sistematis - Dewiga Angkotamony; Setya Haksama; Fariani Syahrul (Malahayati Nursing Journal, 2026)
ABSTRACT The use of mobile health (mHealth) is increasingly emerging as an innovative strategy for improving maternal health, particularly in developing countries with limited access to healthcare services. This study aims to analyse the impact of mHealth interventions on maternal health behaviours and outcomes. Articles published between 2020 and 2026 were systematically reviewed using the Google Scholar, ScienceDirect and PubMed databases. The study was conducted in accordance with the PRISMA 2020 guidelines for systematic reviews. A combination of keywords related to mobile health (mHealth), maternal health, antenatal care, health behaviour and utilisation of health services was used to conduct the literature search. Article selection involved three stages: identification, screening, and assessment of full-text eligibility. The Critical Appraisal Skills Programme (CASP) was used to assess methodological quality. The search yielded 670 articles, of which 21 were analysed. The results showed that mHealth always made things better for mothers and their children. It made them more knowledgeable, and they took their iron supplements more often. It also made them live healthier lives. Furthermore, there was a significant increase in the utilisation of maternal health services, particularly antenatal (ANC) and postnatal (PNC) care, and deliveries attended by healthcare professionals. The impact on clinical outcomes for mothers and infants varied, but there was potential for improvement through indirect mechanisms, and mHealth interventions also enhanced engagement and awareness within the healthcare system. mHealth is an effective intervention in improving health behaviours and the utilisation of maternal services, with the potential to impact clinical outcomes. The integration of mHealth into the healthcare system is necessary to optimise its benefits. Keywords: Mhealth, Maternal Health, Antenatal Care, Health Behaviours.  ABSTRAK Pemanfaatan mobile health (mHealth) semakin berkembang sebagai strategi inovatif dalam meningkatkan kesehatan ibu, khususnya di negara berkembang dengan keterbatasan akses layanan kesehatan. Penelitian ini bertujuan untuk menganalisis dampak intervensi mHealth terhadap perilaku dan outcome kesehatan ibu. Artikel yang diterbitkan antara tahun 2020 dan 2026 ditinjau secara sistematis menggunakan basis data Google Scholar, ScienceDirect, dan PubMed. Studi ini mengikuti desain tinjauan sistematis sesuai dengan pedoman PRISMA 2020. Pencarian literatur dilakukan menggunakan kombinasi kata kunci yang berkaitan dengan mobile health (mHealth), kesehatan ibu, antenatal care, perilaku kesehatan, dan pemanfaatan layanan kesehatan. Seleksi artikel melibatkan tahapan identifikasi, penyaringan, dan penilaian kelayakan teks lengkap. Penilaian kualitas metodologis dilakukan menggunakan Critical Appraisal Skills Programme (CASP). Hasil penelusuran diperoleh 670 artikel dan 21 artikel yang dianalisis. Hasil menunjukkan bahwa mHealth secara konsisten meningkatkan perilaku kesehatan ibu, termasuk pengetahuan, kepatuhan konsumsi suplemen zat besi, serta gaya hidup sehat. Selain itu, terjadi peningkatan signifikan dalam pemanfaatan layanan kesehatan maternal, terutama kunjungan antenatal care (ANC), postnatal care (PNC), dan persalinan oleh tenaga kesehatan. Dampak terhadap outcome klinis ibu dan bayi cenderung bervariasi, namun menunjukkan potensi perbaikan melalui mekanisme tidak langsung. Intervensi mHealth juga meningkatkan engagement dan awareness dalam sistem pelayanan kesehatan. mHealth merupakan intervensi yang efektif dalam meningkatkan perilaku kesehatan dan pemanfaatan layanan maternal, dengan potensi dampak terhadap outcome klinis. Integrasi mHealth dalam sistem kesehatan diperlukan untuk mengoptimalkan manfaatnya. Kata Kunci: Mhealth, Kesehatan Ibu, Antenatal Care, Perilaku Kesehatan.